Policy Experiences and Issues in the Baltics, Russia, and Other Countries of the Former Soviet Union - Citrin, Daniel (Occasional Papers; Occasional Paper, 1995)
This papers reviews the common challenges and key issues in the transition process, including the decline in output and determinants of future growth; the behavior of inflation and velocity and implications for stabilization policy; interenterprise arrears; fixed versus flexible exchange rates in stabilization; external financial assistance; and the political economy of macro stabilization, Russia and the IMF.